A socio-technical evaluation of the effectiveness of social housing energy efficient upgrading in Ireland - Sinnott, Derek (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2015)
This dissertation evaluates the results from a multi-level multidisciplinary study on the effect of energy efficient upgrading on social housing. The National Energy Efficiency Action Plan aims to deliver a 20% national energy saving in accordance with EU 2020 targets. The Irish government is investing heavily in a number of what may be described as 'shallow retrofit' schemes in an attempt to significantly reduce domestic energy consumption and associated carbion dioxide emissions and meet the 2020 targets. Funding is administered through a number of schemes including the 'Social Housing Investment Programme'.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin